The The Role Of Family Support And Self-Efficacy On Self-Care Behavior In The Elderly With Type 2 Diabetes - Ratna Yunita Sari; Umdatus Soleha; Erika Chandra Dewi (Universitas Nahdlatul Ulama Surabaya, 2021)
Introduction: Diabetes self-care is an effort to control type 2 diabetes mellitus. Family support and self-efficacy are needed for elderly people with type 2 diabetes mellitus to increase independence in managing their disease. This study aims to determine the relationship between family support and self-efficacy with self-care behavior in the elderly with type 2 diabetes mellitus at the Elderly Posyandu in Wadungasri Village. Methods: This study is a quantitative study with a correlational analytic research design using a cross-sectional approach. The population in this study was 132 elderly with type 2 diabetes mellitus using a probability sampling method with a technique used simple random sampling and obtained a sample of 100 elderly DM type 2. Results: The results showed that most of the elderly have family support and good self-efficacy. with less self-care behavior. The results of the analysis using the Spearman rank test showed that family support was associated with self-care for people with diabetes mellitus type 2 (p-value = 0.006, ɑ = 0.05). The results of the Spearman rank test analysis showed that self-efficacy was related to self-care for people with diabetes mellitus type 2 (p-value = 0.001, ɑ = 0.05). Conclusion: Family support and self-efficacy gave to elderly people with type 2 diabetes mellitus can influence health behavior patterns that will make self-care behavior well.